2011
DOI: 10.1186/1471-230x-11-144
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and ex vivo effects of propofol on myocardial performance in rats with obstructive jaundice

Abstract: BackgroundResponsiveness of the "jaundiced heart" to propofol is not completely understood. The purpose of this study was to evaluate the effect of propofol on myocardial performance in rats with obstructive jaundice.MethodsMale Sprague-Dawley rats (n = 40) were randomly allocated into two groups, twenty underwent bile duct ligation (BDL), and 20 underwent a sham operation. Seven days after the surgery, propofol was administered in vivo and ex vivo (Langendorff preparations). Heart rate, left ventricular end-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In the present study, we confirmed that bile duct ligation resulted in obstructive cholestasis and jaundice and this model was consistent with previous reports describing marked elevation of the serum total bilirubin in rats responding to bile duct ligation [ 5 , 25 ]. In addition, our result also indicated that obstructive jaundice induced the decreased sensitivity in response to the mechanical nociceptive stimulation 14d and 28d after BDL operation, which was in line with a previous experimental study showing that obstructive cholestasis by bile duct resection in rodents displayed decreased nociception [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we confirmed that bile duct ligation resulted in obstructive cholestasis and jaundice and this model was consistent with previous reports describing marked elevation of the serum total bilirubin in rats responding to bile duct ligation [ 5 , 25 ]. In addition, our result also indicated that obstructive jaundice induced the decreased sensitivity in response to the mechanical nociceptive stimulation 14d and 28d after BDL operation, which was in line with a previous experimental study showing that obstructive cholestasis by bile duct resection in rodents displayed decreased nociception [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hyperbilirubinemia is also associated with increased occurrences of postoperative renal failure and hemorrhagic shock 3 4 . Other than extracellular water depletion, defective vascular reactivity, subclinical myocardial dysfunction and systemic endotoxemia, cardiovascular autonomic dysfunction is also involved in cardiovascular instability 5 6 7 8 9 . Our recent study 10 further demonstrated that both sympathetic and vagal components of arterial baroreflex were depressed in jaundiced patients, which may partially explain the increased susceptibility of cardiovascular instability to the above-mentioned perioperative complications.…”
mentioning
confidence: 99%
“…In OJ patients, the matter turns out completely opposite. Since Green et al described the cardiac injury of OJ firstly in 1986,23 studies afterwards have continuously confirmed that cardiac disfunction is one of the common complications in patients with OJ 24. Experimental studies indicated that effects of bile duct ligation on myocytes including decrease of contraction rates and amplitude leads to cardiac disfunction potentially 25.…”
Section: Discussionmentioning
confidence: 99%